Simultaneous determination of cationic surfactants in disinfectants - S. V. Andreev; A. D. Merkuleva; E. S. Belyaev (Тонкие химические технологии, 2019)
Objectives. Cationic surfactants are one of the classes of substances most commonly used in disinfectants. The trend in recent years has been the use of mixtures of several biocides, which poses new challenges for analytical chemistry. In this study, we describe a method for simultaneous determination in the disinfectants alkyldimethylbenzylammonium chloride (ADBAC), alkyldimethyl(ethylbenzyl)ammonium chloride (ADEBAC), chlorhexidine bigluconate (CHG), and polyhexamethylene biguanide hydrochloride (PHMB).Methods. The proposed method is based on the use of reverse-phase and hydrophilic high-performance liquid chromatography with diode-array detectionResults. The best separation of ADBAC, ADEBAC, and CHG was achieved using a column filled with modified spherical silica gel (5 цт, 4.6 × 250 mm) in gradient elution mode. Acetonitrile and acetate buffer with a pH of 5.4 were used as eluents at a flow rate of 1 ml/min. For the determination of PHMB in the presence of the substances under consideration, hydrophilic high performance liquid chromatography was used. The best separation was achieved on an amine phase column (5 цт, 4.6 × 250 mm) using the same eluents. To determine all the substances under consideration, a diode array detector was used. 3D chromatograms were recorded in the wavelength range from 190 to 400 nm.Conclusions. We have shown that the result of the analysis does not depend on the ratio of cationic surfactants in disinfectants. There is also no influence of N,N-bis-(3-aminopropyl)-dodecylamine (Triamine, TA) and the components most commonly used for the manufacture of disinfectants, which was confirmed by testing the method for analyzing real objects. The linearity range for ADBAC was from 0.0062 to 0.97%, for ADEBAC from 0.000726 to 0.201%, for CHG from 0.0128 to 0.111%, and for PHMB from 0.00311 to 0.0205%. The calculated relative errorfor all determined substances was about 4%.